2014
DOI: 10.1155/2014/716509
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Assay of Tectorigenin with Detergents or ATPase Inhibitors against Methicillin‐Resistant Staphylococcus aureus

Abstract: Tectorigenin (TTR) is an O-methylated isoflavone derived from the rhizome of Belamacanda chinensis (L.) DC. It is known to perform a wide spectrum of biological activities such as antioxidant, anti-inflammatory, anti-tumor. The aim of this study is to examine the mechanism of antibacterial activity of TTR against methicillin-resistant Staphylococcus aureus (MRSA). The anti-MRSA activity of TTR was analyzed in combination assays with detergent, ATPase inhibitors, and peptidoglycan (PGN) derived from S. aureus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Understanding the fine ultrastructure of the bacterial cell wall is important to gain insight into bacterial physiology and the mechanism of action of antibiotics against bacteria (40). Using TEM to observe morphological changes in bacterial cells provides useful insights into the mechanism underlying the activity of antibacterial agents (41). When bacteria cells were treated with URS and OXA, cell membrane disintegration, cell lysis, and release of cytoplasmic contents were observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the fine ultrastructure of the bacterial cell wall is important to gain insight into bacterial physiology and the mechanism of action of antibiotics against bacteria (40). Using TEM to observe morphological changes in bacterial cells provides useful insights into the mechanism underlying the activity of antibacterial agents (41). When bacteria cells were treated with URS and OXA, cell membrane disintegration, cell lysis, and release of cytoplasmic contents were observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DCCD disturbs the H + -translocating sector (F 0 ) of the F 0 F 1 -ATP synthase in coupling membranes [ 32 ]. Most bacteria produce ABC transporters, which comprise an essential uptake system for amino acids in bacteria and are shown to be involved in multidrug resistance including that of MRSA [ 23 , 31 ]. NaN 3 is known to inhibit ATP synthesis in mitochondria and ATP-dependent transport systems such as endocytosis by disrupting electrochemical proton gradients in bacterial cells [ 20 , 24 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether SKN directly bound PGN in S. aureus cell wall, SKN (7.8 μ g/mL, 0.5 MIC) was added together with PGN (1.9–125 μ g/mL) to MRSA cultures as previously described [ 23 ]. Lipopolysaccharide (LPS) was used as negative control; it did not demonstrate inhibitory activity against MRSA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tec, which inhibits the inflammation of acute lung injury in mice, is derived from the Chinese herb Belamcanda chinensis ( Ma et al, 2014 ). Another study has shown Tec antibacterial activity against methicillin-resistant Staphylococcus aureus ( Joung et al, 2014 ). Therefore, Tec may represent a potentially effective option to treat inflammation.…”
Section: Discussionmentioning
confidence: 99%